2005
DOI: 10.1002/nau.20149
|View full text |Cite
|
Sign up to set email alerts
|

How do the prevalences of urogenital symptoms change during pregnancy?

Abstract: Urogenital symptoms occur in almost all women during pregnancy. Whereas the prevalence of overactive bladder symptoms is high and remains stable from early pregnancy on, the prevalences of urinary incontinence symptoms increase with gestational age. Despite the high prevalences of symptoms, the majority of women report not to be bothered by it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
53
5
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 24 publications
16
53
5
14
Order By: Relevance
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 46%
See 1 more Smart Citation
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 46%
“…(13,14) However, it is stated that the greatest impact would be of gestation and type of delivery, which would jeopardize the PF by different mechanisms. (15,16) Some studies show that the UI is common during pregnancy. Sharma et al (17) evaluated 240 primiparae through the same questionnaire used in this study found the presence of urinary symptoms in about 48% of the women studied in the third quarter.…”
Section: Resultsmentioning
confidence: 99%
“…Initial questionnaires (S1) were completed at a mean of 8 weeks gestation (range, [4][5][6][7][8][9][10][11][12][13][14], third trimester surveys (S2) at 30 weeks gestation (range, [24][25][26][27][28][29][30][31][32][33][34][35][36][37], and the final series (S3) at a mean of 30 (range, 24-37) weeks postpartum. Seventy-nine subjects ultimately had a live birth at our institutions, of these three were pregnant again at the time of the final series.…”
Section: Resultsmentioning
confidence: 99%
“…Van Brummen et al [3] have studied 515 null gravid women and found SUI in 18.6 and 42.1% of women in the 12th and 36th weeks of pregnancy, respectively. Studies on primiparas have reported postpartum SUI prevalence rates of 0.7–35% [4,5].…”
Section: Introductionmentioning
confidence: 99%